A High-Phosphorus Diet Moderately Alters the Lipidome and Transcriptome in the Skeletal Muscle of Adult Mice - Grundmann, Sarah M.; Ress, Kerstin; Zimmermann, Lea; Höring, Marcus; Liebisch, Gerhard; Most, Erika; Ringseis, Robert; Eder, Klaus; Justus Liebig University Giessen (My University, 2023)
A high phosphorus intake has been associated with various metabolic disorders, including chronic kidney disease, cardiovascular disease, and osteoporosis. Recent studies have demonstrated the effects of dietary phosphorus on lipid and glucose metabolism. This study investigated the impact of a high-phosphorus diet on mouse skeletal muscle lipid composition and gene transcription. Adult male mice (n = 12/group) received either a diet with an adequate (0.3%) or a high (1.2%) phosphorus concentration for 6 weeks. The lipidome analysis showed that among the 17 analyzed lipid classes, the concentrations of three classes were reduced in the high phosphorus group compared to the adequate phosphorus group. These classes were phosphatidylethanolamine (PE), phosphatidylglycerol (PG), and lysophosphatidylcholine (LPC) (p < 0.05). Out of the three hundred and twenty-three individual lipid species analyzed, forty-nine showed reduced concentrations, while three showed increased concentrations in the high phosphorus group compared to the adequate phosphorus group. The muscle transcriptome analysis identified 142 up- and 222 down-regulated transcripts in the high phosphorus group compared to the adequate phosphorus group. Gene set enrichment analysis identified that genes that were up-regulated in the high phosphorus group were linked to the gene ontology terms “mitochondria” and “Notch signaling pathway”, whereas genes that were down-regulated were linked to the “PI3K-AKT pathway”. Overall, the effects of the high-phosphorus diet on the muscle lipidome and transcriptome were relatively modest, but consistently indicated an impact on lipid metabolism.
Keywords: ddc:640; ddc:360